“PHENOTYPIC EVALUATION OF ANTIFUNGAL SUSCEPTIBILITY PATTERN OF Candida albicans ISOLATED FROM DIFFERENT CLINICAL SAMPLES BY KIRBY-BAUER DISC DIFFUSION AND BROTH MICRODILUTION METHOD TO FLUCONAZOLE AND AMPHOTERICIN B” (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Candidiasis is a major fungal infection where Candida albicans is the major cause of infections in humans. Candida albicans is an opportunistic pathogen under immune-compromised conditions and despite anti-fungal therapies, it has become lethal. Increase in the antimicrobial resistance in C. albicans is a matter of concern as it is in the human microbiome.Aim and Objective: To determine the antifungal susceptibility pattern of Candida albicans isolated from different clinical samples against Fluconazole and Amphotericin B by Kirby Bauer disc diffusion method and Broth microdilution method.Materials and Methods: This was a cross sectional study carried out in the Department of Microbiology at Rama Medical College Hospital and Research Centre Mandhana, Kanpur for a period of 1 year i.e, April 2018 to April 2019. A total of 70 isolates of Candida species from different clincal specimens like blood, BAL, urine, Pus, Et secreation and vaginal secreation were evaluated for its susceptibility against Fluconazole and Amphotericin B using Kirby Bauer disc diffusion method and Broth micro dilution method according to the CLSI guidelines 2018.Results: Out of 70 isolates of Candida species 29 (41.4%) isolates were confirmed to be C.albicans. The ratio of Males 18 (62%) was more as compared to that of the Females 11(37.9%) with the maximum age of 31-40 being affected the most followed by 41-50 and least in the age group above 61 years of age. The number of isolates was maximum in the urine sample. A total of 12 (41.3%) samples of Candida were sensitive and 17 (58.6%) samples were resistant to Amphotericin B & 27(93%) samples of Candida were sensitive and 2(6.8%) samples were resistant to Fluconazole by Kirby bauer disc diffusion method. 28(96.5%) samples of Candida were sensitive and 1(3.4%) sample was resistant to Amphotericin B & 25 (86.2%) samples of Candida were sensitive and 4(13.7%) samples were resistant to Fluconazole by broth microdilution method.Conclusion: The Antifungal susceptibility testing by broth microdilution method revealed that fluconazole was exceedingly resistant against Candida albicans (13.7%) and increasingly susceptible to Amphotericin B (96.5%). Antifungal susceptibility testing may possibly be used to calculate the clinical response, to forecast malfunction in management. Therefore, Proper administration of antifungal drugs should be prioritized only with susceptibility result testing.